2006
DOI: 10.1128/mcb.26.2.389-401.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Epidermal Growth Factor (EGF) Receptor Induces Formation of EGF Receptor- and Grb2-Containing Clathrin-Coated Pits

Abstract: In HeLa cells depleted of adaptor protein 2 complex (AP2) by small interfering RNA (siRNA) to the 2 or ␣ subunit or by transient overexpression of an AP2 sequestering mutant of Eps15, endocytosis of the transferrin receptor (TfR) was strongly inhibited. However, epidermal growth factor (EGF)-induced endocytosis of the EGF receptor (EGFR) was inhibited only in cells where the ␣ subunit had been knocked down. By immunoelectron microscopy, we found that in AP2-depleted cells, the number of clathrin-coated pits wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 43 publications
10
112
1
4
Order By: Relevance
“…Furthermore, the essential role of Grb2 and Cbl proteins in clathrin-mediated internalization of EGFR has been previously demonstrated (10,11,(22)(23)(24)(25)(26). To test whether internalization of the 15KR and 16KR/2RK mutants used the same proteins, Grb2 and Cbl proteins (c-Cbl and Cbl-b) were knocked down by specific siRNA as described in refs.…”
Section: Internalization Of Egfr Lysine Mutants Requires Clathrin Grmentioning
confidence: 99%
“…Furthermore, the essential role of Grb2 and Cbl proteins in clathrin-mediated internalization of EGFR has been previously demonstrated (10,11,(22)(23)(24)(25)(26). To test whether internalization of the 15KR and 16KR/2RK mutants used the same proteins, Grb2 and Cbl proteins (c-Cbl and Cbl-b) were knocked down by specific siRNA as described in refs.…”
Section: Internalization Of Egfr Lysine Mutants Requires Clathrin Grmentioning
confidence: 99%
“…Clearly without EGF stimulation, EGFRs were more mobile on the membrane. Dimerization of EGFRs was believed to the cause of reduced mobility for EGF-stimulated EGFRs (50,63), which also induced endocytosis (64). Although untreated EGFRs were more mobile, their time proportions in Brownian and confined diffusion were similar to those of EGF-stimulated EGFRs (Fig.…”
Section: Distributions Of the Dynamic Parameters Of Egfrmentioning
confidence: 89%
“…Internalization of EGFR was initiated by replacing the media with DMEM containing 10 ng/ml EGF (recombinant human epidermal growth factor, PHG0311L, Thermo Fisher Scientific) (64). As membrane-bound EGFRs were typically internalized within 30 min upon EGF stimulation (78), 2-4 EGFR trajectories (duration ranged from 2-10 min) were typically obtained from each well.…”
Section: Fluorescent Probe Labeling To Egfrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some have reported that downregulation of the 2 subunit of AP-2 did not affect EGFR internalization (Motley et al, 2003), whereas others have found that 2 is important for EGFR downregulation (Huang et al, 2004). There has also been contradiction regarding the importance of the 2 subunit of AP-2 in internalization of the EGFR (Hinrichsen et al, 2003;Motley et al, 2003;Huang et al, 2004;Johannessen et al, 2006). Receptors are believed to be recruited into preexisting clathrin-coated pits.…”
Section: Yxx ) and The Dileucine Based (Consensus Motifs [De]xxxl[li]mentioning
confidence: 99%